Water pressure enhanced sintering of alkaline-earth perovskite ceramics. Issue 9 (November 2015) - Slodczyk, Aneta; Lacroix, Olivier; Colomban, Philippe
Abstract: The alkaline earth-based perovskite ceramics are potential electrolytes for components of electrolysers, fuel cells and CO2 /syngas converters. Their high refractariness is an advantage from the chemical stability point of view but involves high sintering temperature (>1450 °C), detrimental to the co-sintering procedure required to assemble device components. Since the presence of protonic species is not intrinsic to the perovskite structure, the Ln-modified perovskites have to be successfully protonated by exposition of dense (95–99% theoretical density) ceramic pieces to (pressurized) water. We demonstrate that densification of a AZr1− x Ln x O3− δ ceramic can be enhanced by prior exposition of 1200 to 1300 °C pre-fired (porous) ceramics to high water pressure using an autoclave. Autoclave temperature and treatment duration are considered. Thermal expansion measurements reveal that the protonation (200–300 °C under 15–80 bar of water vapour) of previously fired (70–80% of the theoretical density) porous perovskite body (SrZr1− x Yb x O3, x =0.1) enhances the sintering and allows densification at lower temperature. The gain in temperature reaches 200–300 °C. IR and Raman studies show that the film formed on surface consists of (hydrated) alkali-earth oxyhydroxides. Sintering enhancement is assigned to the modification of the material structure close to the grain surface/boundary and to the enhancement of ions mobility at the grain surface/interface.